Socialization Of Clean And Healthy Living Behaviors And Screening Of Non-Communicable Diseases In Efforts To Prevent The Pandemic Covid-19 - Fitriani Kahar; Devi Etivia Purlinda; Djoko Priyatno; Ichsan Hadipranoto; Rachmad Bayu Kuncara (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Coronavirus (COV) is a large family of viruses that cause a slaughter starting from mild to severe symptoms. The disease caused by this virus is called Covid-19. One effort in the prevention of Covid-19's penis is to hold a health protocol and get clean life behavior and sehāt in everyday life. Market Ganesha is one of the traditional markets that functions for buying and selling facilities where many people gather so that it becomes a means of repentance of Covid-19 if the community is a PHB pedagang and not applied health protocols. From the results of the activity it was seen that the community was enthusiastic in participating in the socialization of PHBS and alternately to carry out glucose blood pressure. This socialization activity is not only explained but but also socialization of Gerdik and behavior and obedient to the efforts of nitrance. This activity also completes one of the destinations, namely members of the health examination of residents in the form of blood pressure checks and laboratories (blood glucose examination). New) With the majority of respondents are in the category of 41-50 years and the majority of respondents with female sex. The conclusion is that the trader's society has a risk factor for suffering from the disease not menulus (PTM) especially and diabetes mellitus.